The impact of diagnosis-related group-based medical insurance payment model on the prognosis and nursing care of patients undergoing composite trabeculectomy: a retrospective cohort study - Wang, Yu; Zhang, Yu-yun; Yan, Jie; Ji, Tian-bo; Fan, Luo-dan; Wang, Hai-di; Sun, Tong; He, Dan (Frontiers in Public Health, 2025)
BackgroundThe implementation of Diagnosis-Related Groups (DRG) in China’s medical insurance payment system commenced in May 2019, with 30 pilot cities being selected, including Kunming City of Yunnan Province. As part of the nationwide reform of DRG medical insurance payment methods, hospitals are facing increased pressure to decrease average length of stay and improve efficiency within payment cap of different diseases. This study aims to investigate the influence of the DRG-based medical insurance payment reform on the prognosis and nursing care of patients undergoing composite trabeculectomy.MethodsA retrospective cohort study was conducted on 300 patients who underwent composite trabeculectomy in a Class A tertiary hospital in Yunnan Province between January 1, 2016, and December 31, 2022. Patients were divided into two groups: pre-DRG implementation (DRG group: January 1, 2016 – May 1, 2019) and post-DRG implementation (None-DRG group: May 1, 2019 – December 31, 2022). Data on hospital stay, visual acuity, intraocular pressure, visual field, and retinal nerve fiber layer (RNFL) thickness were collected and analyzed. The relationship between the average length of hospital stay and nursing work patients with composite trabeculae was explored based on the prognostic effect.ResultsThe mean length of hospital stay for DRG group is approximately 8 days, compared to approximately 5 days for None-DRG group. The baseline characteristics of the two patient groups were found to be statistically similar (p > 0.05). When comparing post-operative follow-up indicators at ≤ 6 months after surgery between DRG group and None-DRG group, including visual acuity (p > 0.05), intraocular pressure (p > 0.05), field of view (p > 0.05), and RNFL (p < 0.05), no significant differences were observed from baseline. Similarly, when comparing follow-up indicators after more than 6 months post-surgery between the two groups, visual acuity (p > 0.05), intraocular pressure (p > 0.05), and field of view (p > 0.05) were not significantly different from baseline.ConclusionThis study represents the first empirical validation demonstrating that the implementation of the Diagnosis-Related Groups (DRG)-based medical insurance reform significantly reduced the mean length of hospital stay for patients undergoing compound trabeculectomy (from 8 days to 5 days). Notably, this reform did not exert a statistically significant impact on key prognostic indicators, including postoperative visual acuity and intraocular pressure (p > 0.05). Furthermore, the reform was associated with a marked decrease in hospitalization expenses and nursing costs. These findings offer a robust empirical foundation for refining the DRG policy tailored to ophthalmic care and address a critical gap in the existing literature by providing a comprehensive cost–benefit analysis specific to ophthalmological procedures.